Co-culture with mesenchymal stromal cells increases proliferation and maintenance of haematopoietic progenitor cells - Walenda, Thomas; Bork, Simone; Horn, Patrick; Wein, Frederik; Saffrich, Rainer; Diehlmann, Anke; Eckstein, Volker; Ho, Anthony Dick; Wagner, Wolfgang (Journal of cellular and molecular medicine, 2010)
Mesenchymal stromal cells (MSC) have been suggested to provide a suitable cellular environment for in vitro expansion of haematopoietic stem and progenitor cells (HPC) from umbilical cord blood. In this study, we have simultaneously analysed the cell division history and immunophenotypic differentiation of HPC by using cell division tracking with carboxyfluorescein diacetate N-succinimidyl ester (CFSE). ...
Gesehen am 28.09.2023